Electric Car Frame Body Design Fullset Dynamo Capacity 3.000 Watt With Solidworks Modeling 2020 - Hardianto Hardianto; Ade Sunardi; Ryan Ariansyah (Jakarta Global University, 2022)
The problem of safety and comfort of the means of transportation is closely related to the construction of the main frame of the vehicle. In this study, the frame body of an electric car with a capacity of 3.000 watts is the object of study, in order to determine the simulation of loading on the frame body of an electric car with a capacity of 3.000 watts. The research was conducted using an experimental method with the help of the Solidworks 2020 software. The data analyzed was data from the results of testing the design drawing of a 3.000-Watt electric car body frame designed with Solidworks Software and simulated loading of 50 N, 100 N and 150 N. The simulation results of Von mises stress loading of 50 N with a maximum value of 1,670 x 106 N/m2 are marked in red on the simulation graph, while the minimum value from the simulation results can be concluded directly that is 1,009 x 10-2 N/m2 marked with color blue on the simulation graph. The simulation results of Von mises stress loading of 100 N with a maximum value of 3.43 x 106 N/m2 are marked in red on the simulation graph, while the minimum value from the simulation results can be concluded directly, namely 4.57 x 10-2 N/m2 is marked in blue on the simulation graph. The simulation results of Von mises stress loading of 150 N with a maximum value of 5.018 x 106 N/m2 are marked in red on the simulation graph, while the minimum value from the simulation results can be concluded directly, namely 2.150 x 10-2 N/m2 marked with color blue on the simulation graph.